2021
DOI: 10.1002/cam4.4252
|View full text |Cite
|
Sign up to set email alerts
|

Severe anaphylaxis caused by intravenous anti‐cancer drugs

Abstract: Background The incidence and risk factors of severe anaphylaxis by intravenous anti‐cancer drugs are unclear, whereas those of milder reactions have been reported. Study Design Electronic medical charts of cancer patients who have undergone intravenous chemotherapy between January 2013 and October 2020 in a university hospital were retrospectively reviewed. Non‐epithelial malignancies were also included in the analysis. "Severe anaphylaxis" was judged using Brown's criteria: typical presentation of anaphylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In fact, Kim et al reported an outbreak of severe allergies requiring endotracheal intubation due to a multivitamin supplement containing Cremophor 11. In a retrospective review, the incidence of anaphylaxis with phytonadione (vitamin K1), including Cremophor, was estimated to be 3 cases per 10 000 doses (0.03%),12 and severe allergic reactions to paclitaxel occurred in 9 out of 8894 patients (1%) 13. In clinical practice, it is estimated that 3% (0.03%/1%) of severe anaphylaxis occurrences during paclitaxel administration may be due to allergy to Cremophor.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Kim et al reported an outbreak of severe allergies requiring endotracheal intubation due to a multivitamin supplement containing Cremophor 11. In a retrospective review, the incidence of anaphylaxis with phytonadione (vitamin K1), including Cremophor, was estimated to be 3 cases per 10 000 doses (0.03%),12 and severe allergic reactions to paclitaxel occurred in 9 out of 8894 patients (1%) 13. In clinical practice, it is estimated that 3% (0.03%/1%) of severe anaphylaxis occurrences during paclitaxel administration may be due to allergy to Cremophor.…”
Section: Discussionmentioning
confidence: 99%
“…Reactions to paclitaxel occur in up to 40% of patients without anti‐histamine and steroids premedication and in 1.5% of pre‐medicated patients 133 . The rate of reactions after multiple exposures is 10.7%–18.9% for oxaliplatin, 12%–44% for carboplatin, and 5%–20% to cisplatin 133,135–138 . The rate of carboplatin HSR increases from 1% during the first six cycles to 27% after >6 cycles and sooner for BRCA mutations carriers 51,136,139 …”
Section: Prevalence and Risk Factors Of Da: Specific Drugsmentioning
confidence: 99%
“…In countries such as Germany, mAbs contributes to the top 10 drugs inducing anaphylaxis, 140 which may be related to drug usage patterns and genetic effects. The rate of reactions has been reported as 5%–10% for rituximab; 2%–3% for infliximab; 3%–22% for cetuximab; and 0.6%–5% for trastuzumab 133,135–138 . Risk factors for HSRs to biological agents include the underlying disease, the patient's immune status, degree of humanization, glycosylation pattern, type of sourcing cells, dosing interval, and excipients.…”
Section: Prevalence and Risk Factors Of Da: Specific Drugsmentioning
confidence: 99%
See 2 more Smart Citations